(untitled) (International Journal of Physiotherapy, 2016)
Background: Thoracic outlet syndrome (TOS) is a complex condition characterised by a group of conditions that compress on the neurovascular bundle that enter and leaves the thoracic inlet, interscalene triangle, costoclavicular space and above the pectoris minor that occur above the clavicle. 1-2% is associated with arterial obstruction among the other type of TOS. Symptoms usually annoy extremely by movement of cervical spine and head or by raising upper limb. The main aim of this case report is to reduce the gap in evidence based research and to describe the process and outcomes of conservative management. Methods: As there is no specific test for TOS, the patient was initially assessed with Adson and Roos test. All these test were positive along with MR angiogram and Doppler to confirm A-TOS. Physiotherapy intervention of 6 weeks with following procedure such as massage, warm up, passive stretching, active stretching, hand grip strengthening and cool down. Pain was assessed using VAS scale, strength was assessed using hand dynamometer. Patient was also taught to palpate her own pulse (radial) before intervention. Result: After 6 weeks of intervention patients pain intensity according to the VAS scale was 3, and pulse grade was 3+ that shows pain and pulse in the hand and wrist area were improved significantly. Patients hand grip strength is slightly improved compared to pre intervention using TuKey’s multiple comparison test and it is statistically significant in p<0.001, p<0.01 and p<0.05 respectively. Our results have convinced us that particular approach to the treatment of A-TOS. Conclusion: We concluded that the massage, stretching and hap grip strengthening will improve patient’s condition in Arterial TOS. We also suggested that future research should also focus on arterial TOS due to bony abnormalities and patient’s with arterial luminal defect.